PENERAPAN LAYANAN KONSELING KELOMPOK DALAM MENINGKATKAN SIKAP TANGGUNG JAWAB BELAJAR PADA KELAS X.10 KKO DI SMA NEGERI 1 GROBOGAN - Deva Arta Rifajani; Eka Sari Setianingsih; G. Rahastono Ajie (STKIP Subang, 2023)
This research is motivated by phenomena occurring in the world of education today. The low level of responsible learning attitude of KKO students, such as being lazy about studying in class, often procrastinating on assignments, not paying attention to teacher explanations and being less active in class, makes it difficult for students to achieve academic achievements. Then the lack of hope and aspirations for the future becomes an attitude of responsibility for KKO students who are less diligent in studying. The aim of this research is to find out what influences the responsible learning attitudes of KKO class students during the classroom learning process for class X.10 KKO students at SMA Negeri 1 Grobogan. This type of research uses qualitative research. The subjects used in the research were 29 students because 7 other students were taking part in the TC Competition in Jakarta. The data in this research was obtained through interviews, observations and documentation. Based on the results of research data analysis, there are two types of factors that influence the attitude of responsibility for learning, namely: internal factors consisting of the desire to succeed, encouragement of learning needs, hopes and aspirations and external factors consisting of awards, interesting learning activities, and a conducive learning environment. Then there are still many students who are found who do not have a high attitude of learning responsibility. It is hoped that the suggestions that can be conveyed will increase students' motivation to learn in the classroom and in the field, because it cannot be denied that the importance of having a high attitude of learning responsibility is easy to achieve achievement. Apart from that, there should also be good cooperation between families and schools to help improve the attitude of responsible learning in students.